A Comprehensive Review of Embedded Transmission Pricing Methods Based on Power Flow Tracing Techniques. (9th October 2013) - Khan, Baseem; Agnihotri, Ganga
Abstract : Restructuring of electricity supply industry introduced the concept of deregulation. After deregulation transmission cost allocation is a vital issue. In the available literature, various authors have presented different methods for allocation of transmission cost. This paper presents the review of a variety of methods and algorithm based on the principle of power-flow tracing. For a fair and equitable transmission charge allocation it is necessary to know the quantum of power flowing by each generator and load in line flows. Power flow tracing techniques are mainly based on the concepts of proportional sharing principle, graph theory, circuit theory (Z-bus tracing), optimization approach, relative electrical distance concept, Equilateral bilateral exchange (EBE), and game theory. This paper presents a comprehensive review of all the available literature on the above.